Smart Homes Pro- One stop platform for all home automation needs. - Thaneeru, Divya Sindhuja (2018)
Smarthomespro.co.uk is an e-commerce portal which is currently in the planning stage and intended to be the pioneer of delivering innovative and productive solutions for all smart home needs in UK. This is formulated to be a one-stop platform which will cater to all kinds of requirements related to buying, integrating and configuring smart home devices, helping residents in UK move to live a more towards a more sustainable quality of living.